Psychometric Evaluation of the Chinese Version of Occupational LowBack Pain Prevention Behaviors Questionnaire Among Clinical Nurses: A Validation Study - Zhang, Chunqi; Yang, Zhen; Zhang, Huijun (Frontiers in Public Health, 2022)
Objective: This study aimed to translate and validate of the Chinese version of the Occupational Low Back Pain Prevention Behaviours Questionnaire among clinical nurses. Methods: A total of 1186 clinical nurses were recruited from three provinces in northeast China. The reliability of the translated questionnaire was measured by internal consistency, split-half reliability, and test-retest reliability. The validity of the translated questionnaire was evaluated by content validity index, exploratory factor analysis and confirmatory factor analysis. Results: The Cronbach's α value of the questionnaire was 0.891, and the coefficient values for the six domains ranged between 0.804 to 0.917. The split-half reliability and test-retest reliability were 0.663 and 0.734, respectively. Furthermore, the content validity index of the questionnaire was 0.938. The 6-factor structure, supported by the eigenvalues, total variance explained, and scree plot accounted for 63.038% of the total variance. In the confirmatory factor analysis, as the results of model fitting, 2/df=3.753, RMSEA=0.048, GFI=0.929, AGFI=0.913, TLI=0.934, IFI=0.943, CFI=0.943, PGFI= 0.759, PNFI =0.807. Conclusion: The Chinese version of the Occupational Low Back Pain Prevention Behaviours Questionnaire had suitable reliability and validity among clinical nurses. Under the high prevalence of occupational low back pain, the questionnaire can provide a reference for developing educational intervention plans among clinical nurses.